Profesionalisme Guru Matematika Dalam Meningkatkan Mutu Pendidikan - Fitriani F (Madani: Jurnal Ilmiah Multidisiplin, 2023)
The purpose of this research is to understand the professionalism of teachers as educators and seek to improve it in order to improve the quality of education. The research method used is a literature study based on references related to relevant topics. The following are the results of this study: (1) Indicators of professional teacher success can be seen from the quality of the teacher's process and student learning outcomes, (2) Teacher competence, which includes 5 components, namely: pedagogic competence, personality competence, social competence, professional competence, and leadership competence, is a must for teachers to improve the quality of education, and (3) Conducting upgrading, seminars, workshops or training is an effort that can be made by teachers to increase teacher professionalism.